Salvage surgery for recurrent oropharyngeal cancer: post-operative oncologic and functional outcomes. (2nd December 2015) - Culié, Dorian; Benezery, Karen; Chamorey, Emmanuel; Ettaiche, Marc; Fernandez, Jonathan; Poissonnet, Gilles; Riss, Jean-Christophe; Hannoun-Lévi, Jean-Michel; Chand, Marie-Eve; Leysalle, Axel; Saada, Esma; Sudaka, Anne; et al.
Abstract: Conclusion: Post-operative outcomes of salvage surgery for recurrent oropharyngeal squamous-cell carcinoma (OPSCC) were acceptable. Pathologic overall, T- or N-stage and patient comorbidities were the main predictors of patient clinical outcomes. Objectives: To evaluate post-operative outcomes of salvage surgery in patients with recurrent OPSCC and to determine their predictive factors. Materials and methods: This study retrospectively reviewed the electronic medical records of all patients who underwent salvage surgery for recurrent OPSCC, between 2000–2013, in our institution. Overall survival (OS) and cause-specific survival (SS) were determined by Kaplan-Meier analysis. Predictive factors of post-operative outcomes were investigated by using univariate and multivariate analyses. Results: A total of 34 patients were included in this study. Local and general post-operative complication rates were 26% and 27%, respectively. A high level of comorbidity (Kaplan Feinstein Index: KFI ≥ 2) was the only factor associated with a higher risk of local (p = 0.03) and general (p = 0.04) complications. OS and SS rates at 3 years were 48% and 61%, respectively. In multivariate analysis, pathologic overall stage ≥ III was a significant predictor of OS (p = 0.02) and pathologic T-stage ≥ 3 was a significant predictor of SS (p = 0.01). Mean pre-operative and post-operative DOSS (dysphagia outcome and severity scale) scores were 4.4 and 3.9, respectively.